Dietary supplementation and engaging in physical activity as predictors of coronary artery disease among middle‐aged women. Issue 17 (7th June 2013) - Tsai, Ching‐Ching; Hsieh, Ming‐Hsiung; Li, Ai‐Hsien; Chen, Ping‐Ling; Jeng, Chii
<x xml:space="preserve">Abstract</x> Aim and objectives To explore risk factors for coronary artery disease (CAD) among middle‐aged women in Taiwan. Background Coronary artery disease is a leading cause of death among females. Risk factors for CAD vary due to differences in ethnicity, gender and age. However, few studies have documented risk factors among middle‐aged women. Design We employed a cross‐sectional, comparative study design. Methods Sixty‐five middle‐aged women who were suspected of having CAD and who received cardiac catheterisation were purposively sampled and divided into a CAD group (with at least one coronary artery with > 50% stenosis) and a control group, according to the results of catheterisation. Individual questionnaires regarding their medical history, blood test results, sociodemographic characteristics, metabolism, biomarkers and lifestyle risk factors were administered and quantified. Results The mean age of the 65 women (31 CAD and 34 controls) was 56·2 years. Within the CAD group, there was a greater incidence of women with a history of diabetes mellitus (DM), increased fasting blood glucose and increased diastolic blood pressure. Comparatively fewer women within the CAD category used dietary supplements or had a lower level of physical activity. After adjusting for other confounders, it was discovered that women who used dietary supplements (OR = 0·28; p = 0·04) and engaged in physical activities (OR = 0·16; p = 0·02) were less likely to develop CAD. Conclusions Use of dietary supplements and engaging in physical activities can significantly predict the incidence of CAD among middle‐aged women in Taiwan. Relevance to clinical practice Middle‐aged women should be encouraged to take appropriate dietary supplements and engage in physical activity in order to prevent CAD.